How do necrotic cells expose phosphatidylserine to attract their predators—What’s unique and what’s in common with apoptotic cells - Furuta, Yoshitaka; Zhou, Zheng (Frontiers in Cell and Developmental Biology, 2023)
Phosphatidylserine (PS) is a lipid component of the plasma membrane. It is asymmetrically distributed to the inner leaflet in live cells. In cells undergoing apoptosis, PS is exposed to the outer surfaces. The exposed PS acts as an evolutionarily conserved “eat-me” signal that attracts neighboring engulfing cells in metazoan organisms, including the nematode Caenorhabditis elegans, the fruit fly Drosophila melanogaster, and mammals. During apoptosis, the exposure of PS to the outer surface of a cell is driven by the membrane scramblases and flippases, the activities of which are regulated by caspases. Cells undergoing necrosis, a kind of cell death frequently associated with cellular injuries and morphologically distinct from apoptosis, were initially believed to allow passive exposure of PS through membrane rupture. Later studies revealed that necrotic cells actively expose PS before any rupture occurs. A recent study in C. elegans further reported that the calcium ion (Ca2+) plays an essential role in promoting the exposure of PS on the surfaces of necrotic cells. Moreover, evidence suggests that the increased intracellular Ca2+ activates a PS scramblase for PS exposure. These discoveries indicate that necrotic and apoptotic cells, which die through different molecular mechanisms, employ common and unique mechanisms for promoting the exposure of the same “eat me” signal. This article will review studies about the mechanisms regulating the exposure of PS on the surfaces of necrotic and apoptotic cells and highlight their similarities and differences.